The Translation of Nursery Rhymes into Malay: Forms of Target Text and Techniques of Adjustment (Malay Literature, 2023)
The translation of children’s literature, specifically those focusing on adaptation, has attracted the attention of many scholars in the field of translation studies. However, the studies carried out thus far in the context of Malaysia are limited to the translation of children’s literature in the form of prose only. Taking into account the dearth of studies focusing on children’s literature in the form of verse and the importance of adaptation in cross-cultural translation, this article aims to examine how children’s nursery rhymes are translated from English into Malay, by drawing on nursery rhymes contained in Haji’s Book of Malayan Nursery Rhymes (1939) as the source of data. Specifically, this study aims to identify the forms of target text resulting from the translation of nursery rhymes from English into Malay, and subsequently to discuss the adjustments made in adaptations for the new target readers. To achieve the first objective, the study adopts the framework of forms of target text proposed by Low (2013). Meanwhile, to achieve the second objective, the study relies on Nida’s (1964) techniques of adjustment and Pellatt’s (2013) types of paratext. The findings show that most of the translated nursery rhymes are in the form of adaptation. Adjustments made to the adaptation are mainly in the form of alteration to names of people, places, plants and food items. Adjustments are also made to paratexts, whether external or internal, or whether non-verbal or verbal. This study clearly highlights how texts can be manipulated and how paratexts can be presented to form a text that projects a particular image to the target readers.